Giant lipoleiomyoma-an intimidating entity: case report and literature review - Agarwal, Poojan; Prasad, Shubhra; Chauhan, Devender Singh; Rao, Adla Satya Narayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Lipomatous uterine neoplasms are extremely uncommon lesions with a reported incidence of 0.01% to 0.2%. These lesions frequently pose a diagnostic challenge not only for the clinician but also for radiologists and pathologists alike. Diagnosis requires a multidisciplinary as well as multimodality approach. A 42-year-old peri-menopausal lady presented with abdominal distension, pain and irregular menstrual bleeding. On radiology, an intra-abdodominal hetergenous mass was seen suggestive of neoplastic etiology, possibly intraperitoneal liposarcoma. Microscopy revealed numerous adipocyte clusters intersecting the smooth muscle bundles, diagnostic of lipoleiomyoma. The present case is unusual as the patient had both intramural and broad ligament lipoleiomyoma. Through the present case we revisit clinical and morphological findings of lipoleiomyomas along with review of cases published in literature till date.